P856 Associations of antibiotics, hormonal therapies, oral contraceptives, and long-term NSAIDs with Inflammatory Bowel Disease: results from the Prospective Urban Rural Epidemiology (PURE) study. (30th January 2023) - Narula, N; Wong, E C L; Pray, C; Marshall, J K; Rangarajan, S; Islam, S; Bahonar, A; Alhabib, K F; Kontsevaya, A; Ariffin, F; Co, H U; Al Sharief, W; et al.
Abstract: Background: Several medications have been considered to contribute to the aetiology of inflammatory bowel disease (IBD). This study assessed the association between medication use and risk of developing IBD using the Prospective Urban Rural Epidemiology (PURE) cohort. Methods: This was a prospective cohort study of 133, 137 individuals between the ages of 20-80 from 24 countries. Country-specific validated questionnaires documented baseline and follow-up medication use. Participants were followed prospectively at least every 3 years. The main outcome was development of IBD, including Crohn's disease (CD) and ulcerative colitis (UC). Short-term (baseline but not follow-up use) and long-term use (baseline and subsequent follow-up use) was evaluated. Results are presented as adjusted odds ratios (aOR) with 95% confidence intervals (CI). Results: During the median follow-up of 11.0 years [interquartile range (IQR) 9.2-12.2], we recorded 571 incident cases of IBD (143 CD and 428 UC). Higher risk of incident IBD was associated with baseline antibiotic use [aOR: 2.81 (95% CI: 1.67-4.73), p=0.0001] and hormonal medication use [aOR: 4.43 (95% CI: 1.78-11.01), p=0.001]. Among females, previous or current oral contraceptive use was also associated with IBD development [aOR: 2.17 (95% CI: 1.70-2.77), p=5.02E-10]. NSAID users were also observed to have increased risk of IBD [aOR: 1.80 (95% CI: 1.23-2.64), p=0.002], which was driven by long-term users [aOR: 5.58 (95% CI: 2.26-13.80), p<0.001]. All significant results were consistent in direction for CD and UC with low heterogeneity. Conclusion: Antibiotics, hormonal medications, oral contraceptives, and long-term NSAID use were associated with increased odds of incident IBD after adjustment for covariates.